The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1039/c3md00096f
|View full text |Cite
|
Sign up to set email alerts
|

Design and discovery of 4-anilinoquinazoline ureas as multikinase inhibitors targeting BRAF, VEGFR-2 and EGFR

Abstract: a 4-Anilinoquinazoline ureas were envisaged according to the hybrid-design approach based upon two privileged pharmacophores in kinase drug discovery, i.e. 4-anilinoquinazoline and unsymmetrical diaryl urea. In our structure-activity relationships (SAR) campaign, title compounds were synthesized and profiled in biochemical assay for their kinase inhibitory activity. Title compounds 18-20 were found to be multikinase inhibitors with profound activity against BRAF, BRAF V600E, VEGFR-2 and EGFR.Molecular docking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Among them, compound 111 (Figure ) exhibited significant potency toward BRAF, BRAF V600E, EGFR, and VEGFR-2. Docking studies showed that the compound might nicely fit the DFG-out conformation of BRAF …”
Section: Recent Design Of Urea Derivatives In Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, compound 111 (Figure ) exhibited significant potency toward BRAF, BRAF V600E, EGFR, and VEGFR-2. Docking studies showed that the compound might nicely fit the DFG-out conformation of BRAF …”
Section: Recent Design Of Urea Derivatives In Drug Discoverymentioning
confidence: 99%
“…Docking studies showed that the compound might nicely fit the DFG-out conformation of BRAF. 207 Further modification on the aryl group resulted in diaryl ureas (112) as dual EGFR and VEGFR-2 inhibitors. The SAR studies established that a terminal diaryl urea moiety with a chlorine atom at the ortho-position of the urea group was optimal for high inhibitory potency.…”
Section: Recent Design Of Urea Derivatives In Drug Discoverymentioning
confidence: 99%
“…Several molecules have been reported to show nonselective dual inhibition against both B-Raf and EGFR kinases. 38,39 However, to the best of our knowledge, there is rarely a successful report on the treatment of intrinsic resistant colorectal cancers by using a B-Raf/EGFR dual inhibitor.…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have worked on the design, synthesis, and evaluation of small molecule kinase inhibitors for years (11). Herein, we report on a privileged pharmacophores-based hybriddesign approach to identify novel type II BRAF inhibitors.…”
mentioning
confidence: 99%